Leukocyte, Rather than Tumor-produced SPARC, Determines Stroma and Collagen Type IV Deposition in Mammary Carcinoma - Sangaletti, Sabina; Stoppacciaro, Antonella; Guiducci, Cristiana; Torrisi, Maria Rosaria; Colombo, Mario P. (The Journal of experimental medicine, 2003)
Secreted protein, acidic and rich in cysteine (SPARC), also known as osteonectin or BM-40, is a Ca2+-binding matricellular glycoprotein involved in development, wound healing, and neoplasia. However, the role of SPARC in tumors is ill defined mostly because it is expressed by both tumor and stromal cells, especially inflammatory cells. We analyzed the respective roles of host- and tumor-derived SPARC in wild-type and congenic SPARC knockout (SPARC−/−) mice on a BALB/c genetic background injected into the mammary fat pad with SPARC-producing mammary carcinoma cells derived from c-erB2 transgenic BALB/c mice. Reduced tumor growth but massive parenchyma infiltration, with large areas of necrosis and impaired vascularization were observed in SPARC−/− mice. Immunohistochemical analysis showed a defect in collagen type IV deposition in the stroma of lobular tumors from SPARC−/− mice. Chimeric mice expressing SPARC only in bone marrow–derived cells were able to organize peritumoral and perilobular stroma, whereas reciprocal chimeras transplanted with bone marrow from SPARC−/− mice developed tumors with less defined lobular structures, lacking assembled collagen type IV and with a parenchyma heavily infiltrated by leukocytes. Together, the data indicate that SPARC produced by host leukocytes, rather than the tumor, determines the assembly and function of tumor-associated stroma through the organization of collagen type IV.